Cost effectiveness of screening for intracranial aneurysms among patients with bicuspid aortic valve: a Markov modelling study - Aihua Liu; Xin Tong; Xin Feng; Fei Peng; Hao Niu; Jigang Chen; Mingyang Han; Danfeng Zhang (BMJ Open)
Objective Bicuspid aortic valve (BAV) is common and 7.7%–9.8% of patients with BAV have intracranial aneuryms (IAs) which might lead to a devastating subarachnoid haemorrhage (SAH). We aimed to evaluate different screening and follow-up strategies using magnetic resonance angiography for IAs among patients with BAV.Methods A decision-analytic model was built to evaluate the costs and effectiveness of different management strategies from the Chinese healthcare payer’s perspective. The evaluated strategies included natural history without screening for possible IAs, regular screening and no follow-up for detected IAs, and regular screening with regular follow-up (Screen strategy/Follow-up strategy). Base case calculation, as well as probabilistic, one-way, and two-way sensitivity analyses, were performed.Results According to the base case calculation, natural history had the least cost and effectiveness while Every 5 years (y)/Annual gained the highest cost and effectiveness. Every 10y/Biennial was cost effective when compared with Every 10y/Every 5y under the willingness-to-pay threshold of ¥211 743 (US$30 162). Probabilistic sensitivity analysis showed that Every 10y/Biennial was superior in 88.3% of the cases when compared with Every 10y/Every 5y. One-way and two-way sensitivity analyses proved that Every 10y/Biennial was the dominant strategy under most circumstances.Conclusions Screening for possible IAs among patients with BAV and follow-up for detected IAs would increase the effectiveness. Every 10y/Biennial was the optimal strategy from the Chinese healthcare payer’s perspective.